The Potential of Small, Low- Carbon, Zero- Energy Housing: A Multidimensional Approach - Souaid, Cynthia (A+BE | Architecture and the Built Environment, 2024)
This thesis examines the potential of small, low-carbon, (near) zero-energy dwellings as a solution that would both address sustainability challenges and answer to the growing housing shortage in North-West Europe. It adopts a multidimensional outlook that encompasses institutional, social and technical aspects surrounding the dwellings. The institutional aspect is addressed through an investigation of financial, legislative, technical and cultural barriers to the implementation and uptake of small, low-carbon, zero-energy dwellings. A context specific approach is adopted taking into account contextual peculiarities for the formulation of more refined policy suggestions. The social dimension is addressed first from the perspective of market supply through an investigation of the perceptions of housing professionals. The distinction between perceived versus actual barriers identified by housing professionals is made highlighting a potential dyssynchronisation between policy developments and local practice. Accordingly the study calls for innovation in information dissemination between policy and local practice and between housing professionals themselves. The social dimension is then addressed from the perspective of market demand through an investigation of consumers’ current housing preferences. The assumption stating that, due to an increase in smaller, elderly, and lowerincome households, current housing preferences are leaning towards smaller dwellings is refuted underlining the importance of distinguishing between smallest and smaller dwelling sizes. Lastly, the technical dimension is addressed through conducting a partial life cycle assessment that focuses on the embodied carbon of the dwellings. Both downsizing and the use of low-carbon materials such as timber are investigated as embodied carbon reduction strategies. Together, the three dimensions provide a holistic evaluation of the potential of small, low-carbon, zero-energy dwellings as a solution while addressing the complexity in reaching sustainable outcomes.